Fundamental Analysis and Risk Management Mechanisms on Investment Returns and Investor Satisfaction in the Indonesian Capital Market - Loso Judijanto; Christine Riani Elisabeth; Febriawan Ardi Nugroho; Titik Purwaningtyas (Westscience Press, 2025)
This study investigates the influence of Fundamentals and Risk Management Mechanisms on Investment Returns and Investor Satisfaction in the Indonesian capital market. Samples of 148 were surveyed using a Likert scale ranging from 1-5 to find the relationships among the variables, data was analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The outcomes reveal that both Fundamentals and Risk Management Mechanisms considerably positively influence Investment Returns and Investor Satisfaction. Specifically, Fundamentals have a positive effect on both Investment Returns and Investor Satisfaction, while Risk Management Mechanisms contribute substantially to both Investment Returns and Investor Satisfaction. The findings bring to the fore the fact that strong financial fundamentals, coupled with effective risk management mechanisms, are the bedrock of any investor's success and satisfaction. The study gives useful input to investors, policy, and market participants on ways to ensure the stability of capital markets and investor confidence.